2009
DOI: 10.1111/j.1469-8137.2009.03073.x
|View full text |Cite
|
Sign up to set email alerts
|

Plastic bimodal xylogenesis in conifers from continental Mediterranean climates

Abstract: Summary Seasonal radial‐increment and xylogenesis data can help to elucidate how climate modulates wood formation in conifers. Few xylogenesis studies have assessed how plastic xylogenesis is in sympatric conifer species from continental Mediterranean areas, where low winter temperatures and summer drought constrain growth. Here, we analysed intra‐annual patterns of secondary growth in sympatric conifer species (Juniperus thurifera, Pinus halepensis and Pinus sylvestris). Two field sites (xeric and mesic) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
356
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 400 publications
(418 citation statements)
references
References 39 publications
56
356
2
4
Order By: Relevance
“…5) could be caused by a late peak of earlywood formation in Mongolian sites. This agrees with our knowledge of xylogenesis with maximum rates of tracheid production in Spanish pines occurring in May (Camarero et al 2010). …”
Section: )supporting
confidence: 81%
See 1 more Smart Citation
“…5) could be caused by a late peak of earlywood formation in Mongolian sites. This agrees with our knowledge of xylogenesis with maximum rates of tracheid production in Spanish pines occurring in May (Camarero et al 2010). …”
Section: )supporting
confidence: 81%
“…Then, we calculated a second PCA based on the Pearson correlations obtained by relating the treering variables with monthly climate data (mean temperature, precipitation) to summarize climate-growth and climate-density associations. Climate variables were considered from September prior to tree-ring formation up to October of the growth year based on previous studies on climate-growth relationships and xylogenesis (Kirdyanov et al 2007, Camarero et al 2010. The number of retained principal components in the first PCA was two because they explained at least 50% of the data variance (Jolliffe 2002).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Our results agree with previous dendroecological research performed in P. Mediterranean conifers (Camarero et al 2010). regional scales on precipitation recorded at local scales.…”
supporting
confidence: 83%
“…Climate change is resulting in both positive and negative trends in tree growth, the latter frequently observed in drought-stressed environments (Camarero et al, 2010). The influence of climatic variables on growth can be modified over time (Andreu et al, 2007) and previous studies showed a changing association between climatic variables and growth of Pinus species in the Mediterranean area (Bogino & Bravo, 2008;Vieira et al, 2010;Campelo et al, 2013).…”
Section: Study Areamentioning
confidence: 99%